P300 Acetylates JHDM1A to inhibit osteosarcoma carcinogenesis. Issue 1 (4th December 2019) - Wang, Yongkun; Sun, Baozhen; Zhang, Qiao; Dong, Hang; Zhang, Jingzhe
Abstract: JHDM1A participates in cancer development via demethylate dimethyl histone H3 lysine 36 (H3K36me2). p300 is an intrinsic acetyltransferase. This study explored the acetyltransferase activity of p300 on JHDM1A and analyzed the JHDM1A acetylation on H3K36me2 demethylation in osteosarcoma. Co-immunoprecipitation (CoIP) and immunoblotting assay found that p300 directly acetylated JHDM1A at K409 residue in osteosarcoma MG-63 and HOS cells. Nucleosomes and mononucleosomes were prepared and found that acetylation of JHDMIA disrupted its association with nucleosomes and thereby impaired its capability to induce H3K36me2 demethylation. Moreover, chromatin immunoprecipitation (ChIP) assay discovered that the input levels of H3K36me2 in the promoter regions of p21 and puma were increased after acetylation of JHDM1A, which raised the p21 and puma mRNA levels in the cells. Finally, the analysis of JHDM1A acetylation on osteosarcoma cell proliferation and invasion, along with tumor growth pointed out that acetylation of JHDMIA inhibited the proliferation and invasion of osteosarcoma HOS cells, as well as suppressed the tumor growth of osteosarcoma. In conclusion, the outcomes of our research verified that p300 could directly acetylate JHDM1A at K409 site, which reduces the demethylation of H3K36me2, enhanced the transcription of p21 and puma, and thereby inhibited the growth and metastasis of osteosarcoma.